Room‐Temperature Synthesis of Three Compounds Featuring the [Ge4S10]4– Anion from a Water‐Soluble Thiogermanate Precursor. Issue 37 (10th October 2017) - Danker, Felix; Näther, Christian; Pielnhofer, Florian; Bensch, Wolfgang
Abstract : Applying a new synthetic approach in which transition metal complexes and a thiogermanate source are in different liquid phases resulted in crystallization of three new compounds with the adamantane‐like [Ge4 S10 ] 4– anion at room temperature. In the crystal structure of [Ni(cyclam)]3 [Ni(cyclam)(H2 O)2 ][Ge4 S10 ]2 · 21H2 O (I, cyclam = 1, 4, 8, 11‐tetraazacyclotetradecane), the two different Ni 2+ ‐centered complexes and two unique [Ge4 S10 ] 4– anions are joined by H‐bonding interactions with a water cluster composed of condensed pentameric and hexameric rings. The compound [Mn(2, 2′‐bipy)2 (H2 O)]2 Ge4 S10 · 3H2 O (II, bipy = bipyridine) also contains the [Ge4 S10 ] 4– anion, which is expanded by two Mn 2+ ‐centered complexes through Mn–S–Ge bonds. The aqua ligand of the Mn 2+ ‐centered complex is involved in O–H··· S H‐bonding to a terminal S atom of the anion with formation of a chain of [Mn(2, 2′‐bipy)2 (H2 O)]2 Ge4 S10 molecules. In the structure of [Fe(2, 2′‐bipy)3 ]2 [Ge4 S10 ]· 10H2 O (III ), the [Fe(2, 2′‐bipy)3 ] 2+ complexes are arranged to form channels that host the thiogermanate anions. Between the 2, 2′‐bipy ligands of the complexes π–π interactions are observed. The water molecules of crystallization form two different types of water clusters. Abstract : Three new compounds containing the adamantane‐like [Ge4 S10 ] 4– anion were synthesized at room temperature. Mixing solutions of transition metal complexes in acetonitrile and an aqueous solution of the thiogermanate source resulted in formation of the compounds within short reaction times.